Vaginal foreign bodies in pediatric population - presentation, diagnostic challenges, and role of vaginoscopy: A case series (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Vaginal foreign bodies (VFBs) in the pediatric population pose diagnostic and management challenges. This is due to the usual difficulty in obtaining an appropriate history, difficulty in conducting a vaginal examination, and the fallibility of conventional imaging modalities in picking most of the vaginal foreign bodies. In prepubertal who present with abnormal vaginal discharge or vaginal bleeding, the diagnosis of a vaginal foreign body should be considered, and appropriate care should be provided. Vaginoscopy is an excellent diagnostic and therapeutic modality for these cases.  Case series: Between 2018 and 2023, 6 children aged between 3 and 6 years underwent vaginoscopy at our institution, having presented with diverse vaginal symptoms. The mean age was 4.5 years. Three presented with vaginal bleeding, two had recurrent vaginal discharge, and one had a history of trauma to the genitalia. There were no cases suspicious of sexual abuse. All except two had a normal external genital examination, with one having a small excoriation on the labia and the other having superficial perineal injuries due to trauma. All six cases had intact hymens. Vaginoscopy was performed using a 4-mm scope. Vaginal foreign bodies of varying size and consistency were retrieved from three patients. One patient had inflammatory changes on the proximal anterior vaginal wall. Two had normal findings. All 6 children tolerated the procedure well, with an excellent response to treatment.  Conclusion: Correct diagnosis and management of pediatric vaginal foreign bodies is challenging compared with the adult population. A high index of suspicion is necessary for any young girl presenting with vaginal bleeding or abnormal vaginal discharge. Vaginoscopy is a safe and efficient diagnostic and therapeutic procedure for vaginal foreign bodies in the pediatric population.